Towards a Context-Specific Framework for Family Economic Empowerment: Lessons from Developing Countries - Fayaz Gul Mazloum Yar; Sarani, Hashmatullah (ORGANIZE: Journal of Economics, Management and Finance, 2025)
This study explores effective strategies for family economic empowerment by examining successful models from selected developing countries and assessing their applicability in the Afghan context. Recognizing the persistent socio-economic challenges in Afghanistan—such as poverty, limited access to finance and training, and gender inequality—the research proposes a tailored framework that integrates global best practices with local realities. A mixed-methods approach was employed, combining a quantitative household survey (N=300) with qualitative interviews and focus groups. The quantitative data were analyzed using descriptive and inferential statistics, while thematic analysis guided the qualitative interpretation. Findings indicate a 35% average increase in household income among program participants, improved employment rates, and enhanced financial inclusion. The study applies asset theory and the capability approach to conceptualize economic empowerment and contextualize findings. Despite these outcomes, limitations include a restricted sample size and limited generalizability beyond the surveyed regions. This research contributes to the literature by proposing a culturally embedded, evidence-based model for enhancing family livelihoods in fragile contexts.